The Bornean orangutan (Pongo pygmaeus wurmbii) density in a logging concession of Hulu Belantikan, Central Kalimantan, Indonesia - IMAN SAPARI; DYAH PERWITASARI-FARAJALLAH; SRI SUCI UTAMI ATMOKO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sapari I, Perwitasari-Farajallah D, Utami Atmoko SS. 2019. The Bornean orangutan (Pongo pygmaeus wurmbii) density in a logging concession of Hulu Belantikan, Central Kalimantan, Indonesia. Biodiversitas 20: 878-883. The Bornean orangutan is currently categorized as a critically endangered species. It is found in natural forests in Borneo, where about 78% of the total population is found outside protected areas, of which 29% is in logging concessions. This study aimed to analyze the density of the orangutan population and the abundance of fruiting plants in a logging concession and Protection Forest (Hutan Lindung) in the Hulu Belantikan forests in Lamandau District, Central Kalimantan, Indonesia. Research and data collection was conducted between December 2013 to October 2014. Orangutan population density was calculated using line transect methodology based on nest counts. Abundance of fruit plants was calculated using the fruit trail method. The highest orangutan density, 4.8 individuals/km2, was found in Protection Forest; and the lowest density, 0.4 individuals/km2, was in [Sopanan] the 2013 logging block. Observations in the logging area indicated that selective logging could alter the structure and gap of the canopy and reduce the proportion of large trees. Changes in forest structure resulted in negative effects on the density of the orangutan population. The remaining degraded forests can still be a valuable resource for the orangutan. As long as the disturbance is not intensive, orangutans will retain access to the less disturbed forest nearby and to forests that are still connected to primary forests. The existence of Protection Forest and old logged-over forests around logging blocks are very important for conservation, providing refugia for orangutans and other species when logging occurs.